In-situ removal of aquaculture waste nutrient using floating permeable nutrient uptake system (FPNUS) under mixotrophic microalgal scheme. (November 2022) - Mubashar, Muhammad; Zhang, Junjie; Liu, Qingling; Chen, Liang; Li, Jing; Naveed, Muhammad; Zhang, Xuezhi
Graphical abstract: Highlights: In-situ nutrient removal using mixotrophic FPNUS was evaluated. Mixotrophic N removal rate reached 2.53 mg/(L·d) with PO4 − -P addition. Mixotrophy removed 30.8% and 62.3% more N than autotrophy and BNR. Daily nutrient loading and removal were matched only under mixotrophic FPNUS. Abstract: The current study investigated the in-situ aquaculture nutrient removal from fish tanks using mixotrophic Scenedesmus in a floating permeable nutrient uptake system (FPNUS) and compared with nutrient concentration in control, autotrophy, and bacterial nitrogen removal (BNR) treatments. In the first run, results were not as expected due to the missing PO4 − -P as the mixotrophic growth in flasks with PO4 − -P was 55.86% more than growth in aquaculture wastewater. With PO4 − -P addition in FPNUS, average and maximum removal rates under mixotrophy reached 2.53 and 10.96 mg/(L·d), respectively. The average mixotrophic removal rate was 40.31 and 81.42% higher than removal rates under autotrophy and BNR. Daily nutrient loading and removal were matched only in mixotrophy after fourth day of culture. These results show the great potential for nutrient removal using mixotrophic microalgae-based FPNUS due to its high efficiency, capability of in-situ treatment and nutrient recycling through biomass utilization.